ANALISIS PROSES BERPIKIR KOMBINATORIK SISWA DALAM MENYELESAIKAN SOAL BARISAN DAN DERET PADA SISWA KELAS XI - Wahyuni, Sri; Setiawani, Susi; Oktavianingtyas, Ervin (Department of Mathematics Education , University of Jember, 2018)
The process of combinatorial thinking is one type of thought process that learners must possess. The combinatorical thinking process provides systematic steps in problem solving. This study aims to determine the process of combining student thinking in solving the sequence and series problem. This research is descriptive research with qualitative research. The method used in this research is test and interview. The subject of this study consisted of four students from one classes. Four students represent each level in the combinatorial thinking process. The indicator of the combinatorial thinking process used Students are able to express the concepts of sequence and series, Students are able to explain what is known in the sequence and sequence. Students are able to change the sequence and series into the mathematical sentence. Students are able to write down what is asked in the matter of the line and series, Students are able to solve the problem of sequence and series until the solution or answer, Students are able to answer about the sequence of sequence and series using the concept of sequence and series, Students are able to describe the reason or cause of the answer. Level one students tend to be able to write down what is known and asked questions correctly, second-level students tend to be able to change the known and asked questions at level one with mathematical sentences. Students with level three tend to be able to do the matter with the calculations and concepts correctly, and Students with level four tend to be able to describe and explain the conclusions of the workmanship Keywords: thinking process, combinatorial thinking, sequence and series.